Vapor deposition material and method for manufacturing semiconductor thin film

JP2025036263APending Publication Date: 2025-03-14KISAN KINZOKU +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024145543
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-31
Filing Date
2024-08-27
Publication Date
2025-03-14

AI Technical Summary

Benefits of technology

【0007】 本開示の蒸着材料によれば、十分な透過率を有しつつ特性に優れた半導体薄膜が蒸着により形成可能である。 又、本開示の半導体薄膜の製造方法によれば、十分な透過率を有しつつ特性に優れた半導体薄膜が形成される。 更に、本開示の半導体薄膜の製造方法によれば、十分な透過率を有しつつ特性に優れたp型の半導体薄膜が形成される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036263000001_ABST
    Figure 2025036263000001_ABST
Patent Text Reader

Abstract

To provide a vapor deposition material capable of forming, by vapor deposition, a semiconductor thin film excellent in characteristics while having sufficient transmissivity, and a method for manufacturing the semiconductor thin film, capable of forming a p-type semiconductor thin film excellent in characteristics while having sufficient transmissivity.SOLUTION: A vapor deposition material includes CuI, metal oxide and a dopant. The metal oxide is, for example, at least one of ZrO2, Al2O3 and TiO2; the dopant is, for example, at least one of SnI2 and SnI4; and the semiconductor thin film SC is manufactured by vapor-depositing the vapor deposition material on the film arrangement surface M of a base material B.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to materials for forming light-transmitting semiconductors by vapor deposition, and methods for producing semiconductor thin films. [Background technology]

[0002] A method for forming a transparent conductive film using a transparent conductive film material is known, as described in JP-A-2013-196945 (Patent Document 1). The transparent conductive film material is made by adding zinc oxide to a copper iodide solution in which copper iodide is dispersed in an organic solvent. Then, this transparent conductive film material is applied to an object by any of methods such as spin coating, spray coating, and inkjet coating, thereby forming a transparent conductive film. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2013-196945 A Summary of the Invention [Problem to be solved by the invention]

[0004] 2. Description of the Related Art Semiconductor thin films (particularly p-type semiconductor thin films) that have sufficient transmittance and excellent properties such as mobility are desired for improving the performance of solar cells. When the above-mentioned methods are used to form such a thin film, the thin film becomes a conductive thin film with limited performance improvement.

[0005] Therefore, a main object of the present disclosure is to provide a deposition material for a semiconductor thin film having sufficient transmittance and excellent characteristics. Another main object of the present disclosure is to provide a manufacturing method capable of manufacturing a semiconductor thin film having sufficient transmittance and excellent characteristics. Furthermore, another main object of the present disclosure is to provide a manufacturing method capable of manufacturing a p-type semiconductor thin film having sufficient transmittance and excellent characteristics. [Means for solving the problem]

[0006] The present specification discloses a deposition material. The deposition material may include CuI. The deposition material may include a metal oxide. The deposition material may include a dopant. This specification also discloses a method for producing a semiconductor thin film. In this method for producing a semiconductor thin film, the semiconductor thin film may be deposited by depositing the deposition material described above. In this method for producing a semiconductor thin film, the semiconductor thin film may be formed on a surface of a substrate. Effect of the Invention

[0007] According to the deposition material of the present disclosure, a semiconductor thin film having sufficient transmittance and excellent characteristics can be formed by deposition. Moreover, according to the method for manufacturing a semiconductor thin film of the present disclosure, a semiconductor thin film having sufficient transmittance and excellent characteristics is formed. Furthermore, according to the method for producing a semiconductor thin film of the present disclosure, a p-type semiconductor thin film having sufficient transmittance and excellent characteristics is formed. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a schematic cross-sectional view of a semiconductor member according to an embodiment of the present disclosure. [Diagram 2] 2 is a flowchart showing the manufacturing process of the semiconductor member of FIG. 1. [Diagram 3] 1 is a graph showing the spectral transmittance of a thin film of Example 1 and a thin film of Comparative Example 1. [Figure 4] 1 is a photograph showing an SEM image of the thin film of Example 1. [Diagram 5] 3 is a photograph showing an SEM image of the thin film of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, embodiments of the present disclosure will be described with reference to the accompanying drawings. The description includes modified examples of the embodiments. The present disclosure is not limited to the embodiments and the modified examples.

[0010] The deposition material according to the present embodiment is a material for a semiconductor thin film SC containing copper iodide (CuI) as a main component. Here, the main component is a component having the largest weight ratio among all components. The deposition material according to the present embodiment contains CuI. CuI is preferably a solid, more preferably a powder. 1, a semiconductor thin film SC is formed by depositing the deposition material according to this embodiment on a film mounting surface M of a substrate B. The semiconductor thin film SC may be in contact with the film mounting surface M, or may be formed so as to be in contact with one or more intermediate films formed on the film mounting surface M. The substrate B and the semiconductor thin film SC are components of the semiconductor member P. The shape of the substrate B may be any shape, for example, a plate, a sheet, a film, or a block. The plate-shaped substrate B may be regarded as a substrate. The film placement surface M of the substrate B may be a flat surface, a curved surface, or a combination of a flat surface and a curved surface.

[0011] The semiconductor thin film SC has light transmissivity. The semiconductor thin film SC is semi-transparent or transparent. Preferably, the average transmittance of the semiconductor thin film SC in a specific wavelength range in the visible range is 65% or more, more preferably 75% or more. Here, the visible range is, for example, 400 nm (nanometers) to 780 nm, and the specific wavelength range is, for example, 400 nm to 700 nm. The lower limit of at least one of the visible range and the specific wavelength range may be 380 nm, 390 nm, 410 nm, 420 nm, or 450 nm. The upper limit of at least one of the visible range and the specific wavelength range may be 650 nm, 680 nm, 690 nm, 720 nm, 750 nm, 790 nm, or 800 nm. Furthermore, the lower limit of the average transmittance in the specific wavelength range may be 70%, 80%, 85%, or 90%. The semiconductor thin film SC may be either p-type or n-type, but is preferably p-type. Examples of p-type light-transmitting semiconductor thin film materials include NiO, Cu, 2 O, CuAlO 2 However, the formation of semiconductor thin films using these materials requires heating of the substrate during film formation and annealing treatment after film formation, which is costly and time-consuming.

[0012] Although the thin film formed by vapor deposition using only CuI as the material is made of CuI, gaps are found at the grain boundaries of the multiple particles that make up the thin film. Such gaps impair the continuity of the film, which causes a decrease in transmittance and conductivity. Furthermore, such gaps increase the surface area, which increases the probability of contact with moisture and oxygen in the air, causing relatively rapid deterioration. Furthermore, there is a limit to the improvement of the performance as a semiconductor in a thin film containing only CuI as a component.

[0013] Therefore, a metal oxide is added to the deposition material, and the metal oxide is preferably a solid, more preferably a powder. Although the details of the mechanism are unclear, metal oxides contribute to the formation of a denser thin film compared to when no metal oxide is added. Metal oxides contribute to the uniformity of the particle size of CuI in the deposition material, and it is believed that deposition materials containing metal oxides allow the deposition of dense thin films containing CuI. If the thin film becomes dense, the gaps are reduced, and the decrease in transmittance, decrease in conductivity, and deterioration are suppressed. Metal oxides include, for example, zirconium oxide (zirconia, ZrO 2 ), aluminum oxide (alumina, Al 2 O 3 ), titanium dioxide (titania, TiO 2 ) or at least one of the following. From the viewpoint of forming a sufficiently dense thin film while suppressing costs, the metal oxide is ZrO 2 It is preferable that:

[0014] In addition, an organic compound may be added to the deposition material in place of or together with the metal oxide. The organic compound is preferably in a solid or liquid state, and more preferably in a powder or liquid state. Although the details of the mechanism are unclear, the organic compound contributes to the formation of a denser thin film compared to when the organic compound is not added. The organic compound contributes to the uniformity of the particle size of CuI in the deposition material, and it is believed that the deposition material containing the organic compound allows the deposition of a dense thin film containing CuI. If the thin film becomes dense, the gaps are reduced, and the decrease in transmittance, decrease in conductivity, and deterioration are suppressed. Examples of organic compounds include polyurethane prepolymers, styrene-polycarboxylic acid copolymers, lignin sulfonates, carboxymethylcellulose, acrylates, polystyrene sulfonates, acrylamides, polyvinylpyrrolidone, casein, gelatin, phosphate esters, surfactants (nonionic, cationic, anionic), polyethylene glycol, ethylene-vinyl acetate copolymers, sorbitan fatty acid esters, and sulfosuccinate salts. Furthermore, examples of oligomers and prepolymers include unsaturated polyesters, unsaturated acrylics, epoxy acrylates, urethane acrylates, polyester acrylates, polyether acrylates, polybutadiene acrylates, silicone acrylates, maleimides, polyene / polythiols, and alkoxy oligomers.

[0015] Furthermore, in order to improve the performance as a semiconductor, a dopant that imparts a hole doping effect to CuI is added to the deposition material. The dopant is preferably a solid, more preferably a powder. The dopant is present in the thin film after deposition. The metal oxide and the organic compound each contribute to the dispersion of the dopant in the deposition material, and the deposition using such deposition materials results in a thin film in which the dopant is sufficiently dispersed. The dopant is, for example, SnI 2 and SnI 4 From the viewpoint of further improving the performance as a semiconductor, the dopant is preferably SnI 2 SnI 2 The ionic radius of Sn in Cu 2+ The ionic radius of SnI is smaller than that of 2 In relation to CuI, the hole doping effect is more pronounced.

[0016] The weight ratio of CuI, metal oxide, and dopant may be any, but is preferably 70-90 parts by weight of CuI, 10-30 parts by weight of metal oxide, and 3-10 parts by weight of dopant, where "a-b" indicates a to b. In this preferred range of weight ratio, when the maximum amounts of metal oxide and dopant are added to CuI, the weight ratio becomes CuI:metal oxide:dopant=70 parts by weight:30 parts by weight:10 parts by weight. On the other hand, within this preferred weight ratio range, when the metal oxide and dopant are each added to CuI in a minimum amount, the weight ratio becomes CuI:metal oxide:dopant=90 parts by weight:10 parts by weight:3 parts by weight.

[0017] When an organic compound is used in place of the metal oxide, the preferred weight ratio range is also such that the parts by weight of the metal oxide are regarded as parts by weight of the organic compound. When a metal oxide and an organic compound are used in combination, the preferred weight ratio of CuI, metal oxide, organic compound, and dopant is 40-70 parts by weight of CuI, 10-30 parts by weight of metal oxide, 20-30 parts by weight of organic compound, and 3-10 parts by weight of dopant. In this preferred weight ratio range, when all additives are added in maximum amounts to CuI, the weight ratio is CuI:metal oxide:organic compound:dopant=40 parts by weight:30 parts by weight:30 parts by weight:10 parts by weight. On the other hand, in this preferred weight ratio range, when all additives are added to CuI at a minimum, the weight ratio becomes CuI:metal oxide:organic compound:dopant=70 parts by weight:10 parts by weight:20 parts by weight:3 parts by weight.

[0018] As shown in the upper part of FIG. 2, the deposition material is preferably prepared as follows. That is, first, at least one of a metal oxide, an organic compound, and a dopant is added to CuI (step S1). Next, CuI and the additive are mixed (step S2). This mixture may be in the form of a powder or liquid. Next, the mixture is molded and dried (step S3). The mixture is molded, for example, by placing it in a mold. The molding and drying of the mixture may be performed in parallel, for example by heating the mixture while it is placed in a mold, or may be performed sequentially, for example by placing the mixture in a mold, solidifying the mixture, removing it from the mold, and then heating the mixture. The molding and drying of the mixture may be performed in parallel, and then only the drying step may be performed. Alternatively, the drying step may be omitted. The mixture after molding and drying becomes the deposition material. The deposition material may be in the form of a powder, a pellet, a block, or a liquid. The liquid deposition material may be impregnated into a body such as a porous body.

[0019] As shown in the lower part of FIG. 2, the semiconductor thin film SC is preferably manufactured as follows. That is, the semiconductor thin film SC is formed by evaporating the evaporation material onto the base material B (step S4). The evaporation is preferably vacuum evaporation, and does not involve heating the base material B. The semiconductor thin film SC is formed by a dry method. The ratio of dopant to CuI in the semiconductor thin film SC thus produced is the same as that in the deposition material.

[0020] In the method for producing a semiconductor thin film SC by vapor deposition according to the present disclosure, there is no need to heat the substrate B during film formation, nor any separate processing after film formation, and a light-transmitting semiconductor thin film SC with excellent semiconductor performance can be easily produced at lower cost. EXAMPLES

[0021] Examples belonging to the present embodiment and comparative examples not belonging to the present embodiment are shown below. The following examples are not intended to limit the scope of the disclosure. Depending on how the present embodiment is interpreted, the following examples may essentially be comparative examples, or the following comparative examples may essentially be examples.

[0022] [Example 1 and Comparative Example 1] The deposition material of Example 1 was produced as follows. That is, 75 parts by weight of CuI powder and 25 parts by weight of ZrO powder were mixed. 2 , and 5 parts by weight of powdered SnI 2 was added and mixed to produce a mixed powder. Next, the mixed powder was press-molded to produce a number of compacts. Each compact was pellet-shaped, with a diameter of about 20 mm (millimeters) and a thickness of about 5 mm. Next, each molded body was dried in an environment at 60° C. for 120 minutes to produce a pellet-shaped deposition material.

[0023] The deposition material of Comparative Example 1 was produced as follows. That is, first, 100 parts by weight of CuI powder and 5 parts by weight of SnI powder were mixed. 2 was added and mixed to prepare a mixed powder. In Comparative Example 1, no metal oxide was added. Then, similarly to Example 1, the mixed powder was press-molded to produce a plurality of molded bodies, and each molded body was dried to produce a pellet-shaped deposition material.

[0024] The information regarding the production of the deposition materials of Example 1 and Comparative Example 1 is shown at the top of Table 1 below.

[0025] [Table 1]

[0026] The deposition material of Example 1 and substrate B were then set in an electron beam deposition apparatus, and the electron beam deposition apparatus was driven to form a thin film of Example 1 on one side of substrate B. The deposition rate and physical film thickness during deposition were controlled based on a quartz crystal film thickness meter. The deposition rate was set to 3 to 5 Å / s (angstroms per second). The substrate B was a fused quartz substrate, and had a disk shape with a diameter of 30 mm and a thickness of 1 mm. The physical thickness of the thin film was 100 nm. Similarly, the thin film of Comparative Example 1 was formed on one surface of the substrate B by vapor deposition of the vapor deposition material of Comparative Example 1. The substrate B, the physical thickness of the thin film, and the deposition rate were the same as those in Example 1. In the deposition of Example 1 and Comparative Example 1, no additional treatment such as annealing treatment was carried out after deposition.

[0027] Then, the thin film of Example 1 and the thin film of Comparative Example 1 were evaluated for electrical conductivity, carrier type, mobility, and transmittance. The results of these evaluations are shown in the lower part of Table 1 above. Moreover, the thin film of Example 1 and the thin film of Comparative Example 1 were observed by SEM (scanning electron microscope), and images of the thin film of Example 1 and the thin film of Comparative Example 1 were obtained by SEM.

[0028] The electrical conductivity of the thin films was evaluated according to the following criteria: The conductivity of the thin films was measured using a low-resistance resistivity meter, which measures resistivity by pressing a four-point probe against the surface of the thin film. The unit of conductivity is S / m (Siemens per meter). The electrical conductivity of the thin film of Example 1 was 32.93. The electrical conductivity of the thin film of Comparative Example 1 was 0.254. The electrical conductivity of the thin film of Example 1 is better than that of the thin film of Comparative Example 1 as a semiconductor.

[0029] The thin film carrier types were evaluated according to the following criteria: That is, Hall measurements were performed on the thin film to determine the carrier type. The carrier type of the thin film in Example 1 was p-type. The carrier type of the thin film in Comparative Example 1 was p-type.

[0030] The mobility of the thin films was evaluated according to the following criteria: That is, it was measured using a Hall effect measuring device ("Resitest8308" manufactured by Toyo Technica Corporation). The unit of mobility is cm 2 / Vs (volt-seconds per square centimeter). The mobility of the thin film of Example 1 was 14.8, which was sufficiently high, and demonstrated good performance as a semiconductor. The mobility of the thin film of Comparative Example 1 was 4.54.

[0031] The transmittance of the thin film was evaluated according to the following criteria. That is, the thin film was subjected to a UV-visible spectrophotometer, and the transmittance of the thin film in a wavelength range including the wavelength range of 300 to 900 nm was measured. Fig. 3 is a graph showing the spectral transmittance of the thin film of Example 1 and the thin film of Comparative Example 1. Note that Fig. 3 also shows the spectral transmittance of only the fused quartz substrate. The spectral transmittance of each of the thin films of Example 1 and Comparative Example 1 is sufficiently high at 410 nm or more. As shown in the last line of Table 1, the average transmittance in a specific wavelength range (400 to 700 nm) within the visible range is 78.24% for the thin film of Example 1 and 75.77% for the thin film of Comparative Example 1, both of which are sufficiently high at 75% or more.

[0032] The thin film of Example 1, like the thin film of Comparative Example 1, is formed from a deposition material containing CuI. However, unlike the thin film of Comparative Example 1, the thin film of Example 1 has sufficient conductivity as a semiconductor, a p-type carrier type, sufficiently high mobility, and sufficient transmittance in the visible range.

[0033] FIG. 4 is a photograph showing an SEM image of the thin film of Example 1, and FIG. 5 is a photograph showing an SEM image of the thin film of Comparative Example 1. In the image of Comparative Example 1, many relatively small particles (white to gray) are seen with many gaps (black) between them. Each particle contains a small amount of SnI 2 The particle is made of CuI with added Cu. The minimum diameter passing through the geometric center, which indicates the size of each particle, is less than 100 nm, which is the physical thickness of the thin film. When particles are bonded, the diameter at the bonded part does not need to be taken into consideration when determining the minimum diameter of the particle, and it may be determined that the particle is evenly separated by a virtual plane including the boundary line of the bonded part. The reason why the thin film of Comparative Example 1 has sufficient transmittance despite having many gaps is believed to be as follows. That is, in the thin film of Comparative Example 1, the size of each particle is uniform despite being small, and the gaps between the particles are arranged uniformly even though there are relatively many of them. It is believed that the thin film of Comparative Example 1 having such gaps suppresses the decrease in transmittance in the visible range. However, in the thin film of Comparative Example 1, even if the gaps are arranged uniformly, the movement of charged particles (carriers) is still hindered, and there is a limit to the improvement of performance as a semiconductor.

[0034] In contrast, the image of the thin film of Example 1 shows multiple relatively large particles, and the gaps are reduced compared to the thin film of Comparative Example 1. Each particle is SnI 2 The minimum diameter passing through the geometric center of more than half of the particles is equal to or greater than the physical thickness of the thin film. The thin film of Example 1 was formed by deposition of ZrO 2 Due to the action of the above, some or all of the particles are bonded together to form a film with larger particle size. In the thin film of Example 1, the larger particle size results in fewer gaps. The larger particle size and fewer gaps result in at least one of improved density of the thin film and smoother movement of charged particles, and are considered to contribute to at least one of improved performance as a semiconductor and sufficient transmittance of the thin film of Example 1. From the viewpoint of improving the semiconductor performance of the thin film and / or obtaining sufficient transmittance, it is preferable that the minimum diameter passing through the geometric center of at least half of the particles in the thin film is equal to or greater than the physical film thickness of the thin film. Alternatively, from this viewpoint, it is preferable that the area occupied by the particles whose minimum diameter passing through the geometric center is equal to or greater than the physical film thickness of the thin film when viewed perpendicularly from the front side of the thin film is equal to or greater than half of the area of ​​the entire thin film. The improvement of the performance of the semiconductor may include at least one of high conductivity, p-type carrier type, and high mobility, as well as durability of the thin film. If the size of the particles becomes large and the gap becomes small, as in the thin film of Example 1, the density of the thin film increases, and the durability of the thin film improves.

[0035] Example 1 above is further discussed below. The deposition material of Example 1 contains CuI, a metal oxide, and a dopant, and therefore provides a deposition material that allows a semiconductor thin film SC having sufficient transmittance and excellent characteristics to be formed by deposition. The deposition material of Example 1 contains 75 parts by weight of CuI within a range of 70 to 90 parts by weight, 25 parts by weight of metal oxide within a range of 10 to 30 parts by weight, and 5 parts by weight of dopant within a range of 3 to 10 parts by weight. Therefore, a deposition material is provided that allows a semiconductor thin film SC having more sufficient transmittance and more excellent characteristics to be formed by deposition.

[0036] Furthermore, the metal oxide of the deposition material in Example 1 was ZrO 2 Therefore, ZrO, which is relatively easy to obtain, 2 This makes it possible to obtain a deposition material for depositing a semiconductor thin film SC having sufficient transmittance and excellent characteristics. The dopant of the deposition material in Example 1 was SnI 2 Therefore, the dopant is more compatible with CuI. Furthermore, the deposition material of Example 1 is a molded body formed by mixing CuI, metal oxide, and dopant, all of which are powders, and then molding the mixture. Therefore, the deposition material is easier to handle and more suitable for deposition. In addition, the semiconductor thin film SC formed by the deposition material is of higher quality.

[0037] In addition, by depositing the deposition material of Example 1, the semiconductor thin film SC is manufactured on the film placement surface M of the base material B (Step S4, manufacturing method of the semiconductor thin film SC). Therefore, the p-type semiconductor thin film SC having sufficient transmittance and excellent characteristics can be more easily formed.

[0038] [Example 2 and Comparative Example 2] The deposition material in Example 2 was ZrO 2 It was prepared in the same manner as in Example 1, except for the weight ratio of the powder. In the preparation of the mixed powder of Example 2, 75 parts by weight of CuI powder and 6.25 parts by weight of ZrO powder were used. 2 , and 5 parts by weight of powdered SnI 2 was added.

[0039] The deposition material of Comparative Example 2 was produced as follows. That is, 75 parts by weight of CuI powder and 18.75 parts by weight of ZrO powder were mixed. 2 was added and mixed to prepare a mixed powder. In Comparative Example 2, no dopant was added. Then, similarly to Example 1, the mixed powder was press-molded to produce a plurality of molded bodies, and each molded body was dried to produce a pellet-shaped deposition material.

[0040] The information regarding the production of the deposition materials of Example 2 and Comparative Example 2 is shown at the top of Table 2 below.

[0041] [Table 2]

[0042] Then, the deposition material of Example 2 and the above-mentioned substrate B were set in an electron beam deposition apparatus, and the electron beam deposition apparatus was driven in the same manner as in Example 1, to form a thin film of Example 2 on one side of substrate B. Substrate B and the deposition rate were the same as in Example 1. However, the physical thickness of the thin film of Example 2 was set to 180 nm. Similarly, the thin film of Comparative Example 2 was formed on one surface of the substrate B by vapor deposition of the vapor deposition material of Comparative Example 2. The substrate B, the physical thickness of the thin film, and the deposition rate were the same as those in Example 2. In the deposition of Example 2 and Comparative Example 2, no additional treatment such as annealing was carried out after deposition.

[0043] The thin film of Example 2 and the thin film of Comparative Example 2 were subjected to evaluation of electrical conductivity, carrier type, mobility, and transmittance in the same manner as the thin film of Example 1 and the thin film of Comparative Example 1. The results of these evaluations are shown in the lower part of Table 2 above.

[0044] The electrical conductivity of the thin film of Example 2 was 24.81. The electrical conductivity of the thin film of Comparative Example 2 was 17.48. The electrical conductivity of the thin film of Example 2 is better than that of the thin film of Comparative Example 2 as a semiconductor.

[0045] The carrier type of the thin film in Example 2 was p-type. The carrier type of the thin film in Comparative Example 2 was p-type.

[0046] The mobility of the thin film of Example 2 was 5.56, which was sufficiently high, indicating good performance as a semiconductor. The mobility of the thin film of Comparative Example 2 was 4.6.

[0047] The average transmittance in a specific wavelength range (400 to 700 nm) within the visible range in Example 2 and Comparative Example 2 is, as shown in the last line of Table 2, 66.5% for the thin film of Example 2 and 74.7% for the thin film of Comparative Example 2, both of which are sufficiently high at 65% or more.

[0048] The thin film of Example 2, like the thin film of Comparative Example 2, is formed from a deposition material containing CuI. However, unlike the thin film of Comparative Example 2, the thin film of Example 2 has sufficient conductivity as a semiconductor, a p-type carrier type, sufficiently high mobility, and sufficient transmittance in the visible range.

[0049] Example 2 above is further discussed below. The deposition material of Example 2 contains CuI, a metal oxide, and a dopant, and therefore provides a deposition material that allows a semiconductor thin film SC having sufficient transmittance and excellent characteristics to be formed by deposition.

[0050] Furthermore, the metal oxide of the deposition material in Example 2 was ZrO 2 Therefore, ZrO, which is relatively easy to obtain, 2 This makes it possible to obtain a deposition material for depositing a semiconductor thin film SC having sufficient transmittance and excellent characteristics. The dopant of the deposition material in Example 2 was SnI 2 Therefore, the dopant is more compatible with CuI. Furthermore, the deposition material of Example 2 is a molded body formed by mixing CuI, metal oxide, and dopant, all of which are powders, and then molding the mixture. Therefore, the deposition material is easier to handle and more suitable for deposition. In addition, the semiconductor thin film SC formed by the deposition material is of higher quality.

[0051] In addition, by depositing the deposition material of Example 2, the semiconductor thin film SC is manufactured on the film placement surface M of the base material B (Step S4, manufacturing method of the semiconductor thin film SC). Therefore, the p-type semiconductor thin film SC having sufficient transmittance and excellent characteristics can be more easily formed.

[0052] Subsequently, the above Examples 1 and 2 are further considered below. The conductivity and mobility of the thin film formed by Examples 1 and 2 containing three components, CuI, metal oxide, and dopant, are better than those of the thin film formed by Comparative Example 1 containing only CuI and dopant, and those of the thin film formed by Comparative Example 2 containing only CuI and metal oxide. Therefore, it is found that the deposition material containing three components, CuI, metal oxide, and dopant, is superior. Moreover, the amount of metal oxide in Example 2 is 6.25 parts by weight, which is outside the range of 10 to 30 parts by weight, whereas the amount of metal oxide in Example 1 is 25 parts by weight, which is within the range of 10 to 30 parts by weight. The electrical conductivity and mobility of the thin film formed in Example 1 are better than those of the thin film formed in Example 2. Therefore, it can be said that the above three-component deposition material in which the amount of metal oxide falls within the range of 10 to 30 parts by weight is even more excellent. [Explanation of symbols]

[0053] B··Substrate, M··Film placement surface, P··Semiconductor material, SC··Semiconductor thin film, S4··Deposition step of deposition material.

Claims

1. Contains CuI, metal oxides and dopants A vapor deposition material characterized by:

2. The composition contains 70 to 90 parts by weight of CuI, 10 to 30 parts by weight of the metal oxide, and 3 to 10 parts by weight of the dopant. The vapor deposition material according to claim 1 .

3. The metal oxide is ZrO 2 , Al 2 O 3 , and TiO 2 At least one of The vapor deposition material according to claim 1 .

4. The dopant is SnI 2 and SnI 4 At least one of The vapor deposition material according to claim 1 .

5. The CuI, the metal oxide, and the dopant, all of which are powders, are mixed and molded to form a compact. The vapor deposition material according to claim 1 .

6. By depositing the deposition material according to any one of claims 1 to 5, a semiconductor thin film is deposited on the film-mounting surface of the substrate. A method for producing a semiconductor thin film, comprising:

Citation Information

Patent Citations

  • Transparent conductive film material, transparent conductive film, and electronic device

    JP2013196945A